Revisionisme Sejarah Jepang terhadap Peristiwa Pembantaian Nanjing - Nanda, Ni Putu Rianti Sukma; Purnomo, Joko (Jurnal Transformasi Global, 2020)
This study examines Japan's historical revisionism related to the Nanjing Massacre during its 1937 invasion in the People's Republic of China. In 2015, UNESCO's response to include the Nanjing Massacre in the "Memory of the World Register" received backlash from Abe's government, resulting in a budget suspension from Japan. Japan wanted to be seen as a good country, leaving behind its past image as a war aggressor through historical revisionism. Using the concept of Shared Beliefs and Therapeutic Value, this article analyses homogeneous Japanese society that regards the Nanjing Massacre as something the Japanese government should not be apologetic about and the heterogeneous historical facts of the massacre itself. Finding suggests that Therapeutic Value from the denial comes from the failure of the U.S. and its allies to provide a deterrent effect post-WWII that resulted in victimization and melodrama promoted by the Japanese government. The government also uses narratives such as Toa Renmei Ron and Kami no Kuni as the main argument to boost Japanese superiority as a country. However, such revisionist strategy of the Nanjing Massacre is proven a failure to promote peace among the younger generation.